PENGATURAN ORGANISASI KERJA HOUSEKEEPING DENGAN PENDEKATAN ERGONOMI DAPAT MENURUNKAN KELUHAN MUSKULOSKELETAL, KELELAHAN, DAN MEMPERCEPAT WAKTU KERJA - Tabita, Angelin; Adiputra, Nyoman; Sutarja, I Nyoman (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 3 No 1 (2017): Volume 3 No 1 Juni 2017DO - 10.24843/JEI.2017.v03.i01.p05, 2017)
This study aims to approve that the reschedule of housekeeping work shifts based on ergonomics may decrease musculoskeletal disorders, decrease fatigue level, and  increase work speed. The reschedule of Housekeeping work shifts conducted by adding more housekeeping workers when cleaning the rooms. The housekeeping formerly was cleaned each room by himself and now scheduled to work by two people, so the task may be shared both. The hotel didn't needed to add new housekeeping workers, just need to reschedule the existing housekeeping , so that the hotel does not need to incur additional costs to conduct work shift with this ergonomic approach.               The research model is design experimental treatment by subject design. The data of musculoskeletal disorders and fatigue level was collected by using a questionaire. The data of work speed was collected by using direct observation to 10 housekeeping workers in Natya Hotel - Bali, as a sample that randomly selected. The tests were conducted using normality test and significancy test with SPSS for Windows 16 th version.                 The results showed that the mean of musculoskeletal disorders in the first period was 57.6 ± 2.59 become 27.1 ± 2.47 in the second period (p < 0.05) or decrease by 36.31%. The mean of fatigue level in the first period was 60.5 ± 2.55 become 27.7 ± 3.23 in the second period (p < 0.05) or decrease by 36.44%. The work speed average in the first period was 21.12 ± 0.06 minutes, while the second period was 13.08 ± 0.03 minutes (p < 0,05) or increase by 23.52%.